Marketing Strategies to Increase Seller Interest in the Cuan Market Event Organizer in Surabaya - Madona Diadora; Yuniardi Rusdianto (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
The event organizer industry in Indonesia is experiencing rapid growth as the public's demand for well-organized, safe, and enjoyable events increases. One emerging trend is thrifting, the buying and selling of secondhand clothing that supports a sustainable lifestyle. Cuan Market is a community-based event organizer with a creative concept and a focus on thrift fashion trends. In an effort to attract visitors and sellers, Cuan Market actively utilizes social media, particularly Instagram, to build a strong brand image and reach a broad audience. Although this strategy has proven effective in increasing exposure, Cuan Market still faces various challenges such as high competition, changing market preferences, and other external factors. This study aims to analyze the marketing strategies used by Cuan Market to retain and attract seller participation. The results of this study are expected to contribute to the development of marketing studies in the context of community events and serve as a practical reference for organizers of similar events in Indonesia.